Plasma prolactin axis shift from placental to pituitary origin in late prepartum mice - Taku James Sairenji; Shinnosuke Masuda; Yuya Higuchi; Mitsue Miyazaki; Hiroyuki Yajima; Oh Kwan Ee; Yuki Fujiwara; Takuya Araki; Noriaki Shimokawa; Noriyuki Koibuchi (Endocrine Journal)
The placenta secretes a prolactin (PRL)-like hormone PRL3B1 (placental lactogen II), a luteotropic hormone essential for maintaining pregnancy until labor in mice. A report from 1984 examined the secretion pattern of PRL3B1 in prepartum mice. In the current study, we found contradictory findings in the secretion pattern that invalidate the previous report. By measuring maternal plasma PRL3B1 and PRL every 4 hrs from gestational day 17 (G17), we newly discovered that maternal plasma PRL3B1 levels decrease rapidly in prepartum C57BL/6 mice. Interestingly, the onset of this decline coincided with the PRL surge at G18, demonstrating a plasma prolactin axis shift from placental to pituitary origin. We also found that maternal plasma progesterone regression precedes the onset of the PRL shift. The level of Prl3b1 mRNA was determined by RT-qPCR in the placenta and remained stable until parturition, implying that PRL3B1 peptide production or secretion was suppressed. We hypothesized that production of the PRL family, the 25 paralogous PRL proteins exclusively expressed in mice placenta, would decrease alongside PRL3B1 during this period. To investigate this hypothesis and to seek proteomic changes, we performed a shotgun proteome analysis of the placental tissue using data-independent acquisition mass spectrometry (DIA-MS). Up to 5,891 proteins were identified, including 17 PRL family members. Relative quantitative analysis between embryonic day 17 (E17) and E18 placentas showed no significant difference in the expression of PRL3B1 and most PRL family members except PRL7C1. These results suggest that PRL3B1 secretion from the placenta is suppressed at G18 (E18).